2019
DOI: 10.1080/02640414.2018.1513355
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of talent development in alpine ski racing: a narrative review

Abstract: Alpine ski racing is one of the most popular sports in many countries; nevertheless, selection disadvantages and severe injuries result in high dropout rates. In this review we summarize existing knowledge about the specific challenges associated with selection bias and injuries, and their effects on talent development in ski racing.The relative age effect (RAE) appears in all age categories of national Austrian and international alpine ski racing. Relatively younger athletes seem to only have a chance for sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 42 publications
2
20
0
7
Order By: Relevance
“…Studies performed with ski racers younger than 15 years of age found the following significant injury risk factors. Athletes with weaker core flexion strength and weaker neuromuscular control were at a higher injury risk in general (10)(11)(12)(13)(14) year old athletes) [6] or had a higher risk of sustaining an ACL rupture (15)(16)(17)(18)(19) year old athletes) [8]. A decreased neuromuscular control of the knee was found to predict the risk of sustaining an ACL injury in female athletes [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed with ski racers younger than 15 years of age found the following significant injury risk factors. Athletes with weaker core flexion strength and weaker neuromuscular control were at a higher injury risk in general (10)(11)(12)(13)(14) year old athletes) [6] or had a higher risk of sustaining an ACL rupture (15)(16)(17)(18)(19) year old athletes) [8]. A decreased neuromuscular control of the knee was found to predict the risk of sustaining an ACL injury in female athletes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when considering the multifactorial nature of injury causes in a changing outdoor environment, which decreases the chance of identifying statistically significant risk factors, as underlined by Spörri et al [2], some risk factors could already be revealed, but a lot of work still has to be done, as for example identifying other athlete-related, equipment-related, or course-setting-related risk factors, elaborating possible prevention measures etc. [11]. Among these, modifiable risk factors such as changes in physical fitness parameters are of special interest for coaches.…”
Section: Introductionmentioning
confidence: 99%
“…Estos estudios confirman que esta capacidad motora no se ve afectada significativamente por la maduración en niños y la existencia de diferencias altamente significativas a los 11 años, dentro del intervalo comprendido entre los 12 y 14 años, en niñas. El motivo de estas diferencias entre niños y niñas podría estar relacionado con la diferente maduración biológica existente en estas edades y con el efecto de la edad relativa en los test motores y en el rendimiento en esquí alpino (Gorski et al, 2014;Müller et al, 2015a;Steidl-Müller et al, 2017, 2019.…”
Section: Discussionunclassified
“…Journal of Physical Education and Human Movement, 1(2) 16-36. ISSN: 2659-5699 DOI: 10.24310/JPEHMjpehm.v1i2.6394 relativa en esquiadores adultos (Bosco, 1994(Bosco, , 1997Ruiz de Almirón et al, 2002;Raschner et al, 2008Raschner et al, , 2013Müller et al, 2015b;Steidl-Müller et al, 2017, 2019. Esto demostró que esta capacidad requiere niveles de fuerza explosiva y reactiva elevados durante los cambios de dirección en el esquí durante la bajada.…”
Section: Discussionunclassified
See 1 more Smart Citation